Quantum Chemical, Vibrational Spectroscopic and Molecular Docking Studies of 1-(Diphenylmethyl)Piperazine - Raajaraman, B R.; Sheela, N. R.; Muthu, S. (Polycyclic aromatic compounds, 2022)
The experimental spectral studies and quantum level theoretical studies were carried out by Density Functional Theory on the compound 1-(diphenylmethyl)piperazine (1DPMP). The optimized geometry and the vibrational frequencies have been computed by the Density Functional Theory with B3LYP method and 6-311++G(d,p) basis set. The observed values of 1 H and 13 C chemical shifts were compared with the theoretical method called Gauge-Independent Atomic Orbital. The topological studies on the 1DPMP have been carried out by Atoms In Molecules theory. The stability of the compound is determined by Natural Bond Orbital analysis. By using Time-Dependent Density Functional Theory mechanism, the maximum absorption wavelength was obtained and compared with the UV-Vis experimental spectrum. By using the frontier molecular orbitals, the energy values and all other important parameters were elucidated. The NonLinear Optical characteristics such as dipole moment, polarizability, and hyperpolarizability of 1DPMP were analyzed by changing the keyword on the same basis set. The reactive areas around the molecule were found by Molecular Electrostatic Potential studies. Furthermore, ADME studies have also been carried out. The best orientation of ligand-protein has been performed by the molecular docking process with the ligand 1DPMP to find the anti-cancer activity with JAK3 and Filaggrin proteins.